Lack of Braf V600e protein expression in primary central nervous system lymphoma - Bergmeister-Berghoff, Anna Sophie; Capper, David; Preusser, Matthias (Applied immunohistochemistry & molecular morphology, 2013)
Mutations in the v-raf murine sarcoma viral oncogenes homolog B1 (BRAF), most commonly of the V600E type, are present in a variety of human malignancies including malignant melanoma, papillary thyroid cancers, and hairy-cell leukemia and specific therapeutically active BRAF inhibitors exist. We aimed to investigate BRAF V600E protein expression in primary central nervous system lymphoma (PCNSL). We investigated BRAF V600E expression in formalin-fixed and paraffin-embedded surgical tissue specimens of 20 immunocompetent patients with PCNSL using the mutation-specific monoclonal mouse antibody VE1. Ten male and 10 female patients with a median age of 60 years (range, 44 to 71 y) at time of operation were included. All cases were qualified as diffuse large B-cell lymphomas. None of the investigated cases demonstrated specific immunoreactivity for BRAF V600E mutation. Our data provide evidence that the BRAF V600E mutation is not pathobiologically relevant in PCNSL and as a consequence is not a feasible drug target in this tumor type.